“SYNTHESIS, INSILICO STUDY & ANTI-PROLIFERATIVE ACTIVITY OF NEW DERIVATIVES OF TRI-ARYL IMIDAZOLE” - Mr. Sandeep P. Gadhwe; Rajesh B. Patil; Chetan S Shirbhate; Govind Kankawale (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study focuses on the process of Docking, Synthesis, and Characterization of novel chemotherapeutic agents with the potential Anticancer Activity. The aim is to discover new compounds for the anticancer activity using MCF7 cell lines on Breast Cancer that exhibit promising properties for Cancer Treatment. Imidazole offers better pharmacodynamic characteristics and directly affect membranes at high concentrations, independent of sterols and sterol esters. Recent developments in imidazole derivatives for drug development show improved efficacy & lower toxicity. The docking approach to assess the binding affinity and interaction between compounds & Protein. Radziszewski synthesis scheme with substituted benzyls and quinoline aldehyde employed to create imidazole compounds. The synthesized Compounds are subsequently analyzed using various techniques like NMR (1H), TLC, FT-IR, Mass Spectral data, Biological evaluation to assess their ability to inhibit cancer cell growth or induce cancer cell death. The findings obtained from this study seek to make a valuable contribution to the advancement of novel chemotherapeutic agents with improved anticancer properties.